2012
DOI: 10.1159/000339000
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rotigotine on Cardiovascular Autonomic Function in Early Parkinson’s Disease

Abstract: Dysautonomia can occur in early stages of Parkinson’s disease (PD) influencing tolerance to dopaminergic therapies. Rotigotine, a non-ergot dopamine agonist, has recently been developed as an effective alternative antiparkinsonian drug, but its influence on the autonomic nervous system was not investigated. Twenty subjects out of 34 consecutive de novo PD patients were submitted to full assessment of cardiovascular autonomic function before and after reaching a stable rotigotine regimen [6 mg/24 h (n = 3) or 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Respiration rate was also monitored continuously using a nasal thermocouple respiration flow sensor (SleepSense ® ). AFTs were performed using standard procedures . The results of each test were automatically calculated by means of Light‐SNV software ® .…”
Section: Methodsmentioning
confidence: 99%
“…Respiration rate was also monitored continuously using a nasal thermocouple respiration flow sensor (SleepSense ® ). AFTs were performed using standard procedures . The results of each test were automatically calculated by means of Light‐SNV software ® .…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that dopamine receptors (D1–D5) are specifically involved in the regulation of blood pressure [ 22 ]. In addition, rotigotine is reported not to influence cardiovascular autonomic responses in de novo PD patients [ 23 ]. Consequently, the major reason for the improvement of postural instability and ADLs in patients treated with rotigotine in this study could be due to lower occurrence of these AEs and the pharmacological property of rotigotine that includes a well-balanced response to all dopamine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 5% of the subjects in the ropinirole 24-h prolonged release group had OH, while 2% of the placebo group had OH. Rotigotine showed no influence on cardiovascular autonomic function in PD in a recent study [80]. Further studies on the influence of anti-PD medication to the cardiovascular autonomic function, especially those using comprehensive examinations, are warranted.…”
Section: Treatment For Cardiovascular Autonomic Dysfunction In Pd Trementioning
confidence: 91%